Implementasi Media Pembelajaran Menggunakan Aplikasi Macromedia Flash 8 Pada Materi Bangun Ruang Sisi Datar - Nabilla Vanesya Meilinda; Lutfiana Fitri Nuraisyah; Eka Senjayawati (Departement of Mathematics Education, 2019)
This research is development research that aims to produce mathematics learning media using macromedia flash software on geometry material and find qualitymedia based on the assessment of learning experts, media experts, students. The development model used is descriptive procedural development model, steps that must be followed to produce a product that starts with standard content analysis followed, collecting references, designing media and creating learning media. The learning media validated by material and learning expert, media experts. The researchers have succeeded developing learning media is packaged in CD containing competency standards to understand the properties of cubes, cuboid, prisms,pyramid determine part and size. According to the assessment of media experts, the media learning material developed has very good quality (SB) with a score of 140.9 with an ideal percentage of 82.888% so it is suitable for use as a learning media.